PERAN ” EKA LAK THAI” DALAM DEMOKASI DI THAILAND - Anna Yulia Hartati (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract This article describes the Role of "Eka Lak Thai" in the development of democracy in Thailand. The author uses qualitative research methods, where the author makes a description, description or painting systematically, factually, accurately about the facts, the properties and relationships between phenomena that are investigated through literature. Thais, Buddhists and Kings are an inseparable part of Thai society which is dictated in the constitution. This has caused democracy in Thailand to be carried out autonomously not absolutely because there is no separation between religion and state, making it difficult for the implementation of democracy. Thai democracy is only ceremonial because it does not open space for freedom of opinion, because the existing tradition is not just a social attribute that can be easily accepted, but the existence of state convictions in Thailand has hardened and become a political identity that fills all space, both political space and social space society. Keywords: Thai Democracy, Eka Lak Thai, Political Identity